Randomised controlled crossover trial of humidified continuous positive airway pressure in mild obstructive sleep apnoea. Issue 5 (28th April 2005) - Marshall, N S; Neill, A M; Campbell, A J; Sheppard, D S
Abstract : Background: It is unclear whether continuous positive airway pressure (CPAP), the treatment of choice for severe obstructive sleep apnoea (OSA), is effective at improving outcomes in mild OSA. Methods: To help define the role of humidified CPAP in mild OSA, a randomised crossover study was undertaken of patients with an apnoea hypopnoea index (AHI) of 5–30/hour. Subjective sleepiness, objective wakefulness, mood, reaction time, and quality of life were measured at baseline, after 3 weeks treatment with humidified CPAP and 3 weeks sham CPAP (2 week washout). Results: Twenty nine of 31 enrolled patients (age 25–67 years, seven women, mean (SD) body mass index 31.5 (6) kg/m 2 ) completed the protocol. Humidified CPAP improved polysomnographic indices of OSA and Epworth Sleepiness Scale (2.4 points (95% CI 0.6 to 4.2)). Objective wakefulness (modified maintenance of wakefulness test) showed a trend towards improvement (5.2 minutes (95% CI −0.6 to 11)). Mood (Hospital Anxiety and Depression Scale), quality of life (SF 36, Functional Outcomes of Sleep Questionnaire), and reaction times (Psychomotor Vigilance Task) were not improved more than sham CPAP. Compliance with humidified and sham CPAP both averaged 4.9 hours/night. Placebo effects were evident in many outcomes and there was no clear treatment preference. Conclusions: Humidified CPAP improves subjective sleepiness and possibly objective wakefulness but not reaction times, quality of life, or mood. These results do not support the routine use of CPAP in all patients with mild OSA, but offers some support for the trialling of CPAP in those with severe sleepiness.